The Effect of Psychological Skills Training on Performance, Retention and Transfer under Pressure of Novice Badminton Players - Ebrahim Moteshareie; Behrouz Abdoli; Seyed Mohammad Kazem Vaez Mousavi; Alireza Farsi (University of Tehran, 2018)
The aim of this study was to evaluate the effect of PST on performance, retention, and transfer under pressure of novice badminton players. 40 novice badminton players were randomly assigned to experimental (20 participants) and placebo-control (20 participants) groups. In acquisition and retention tests, short and long service, toss clear and drop shots were used; in transfer under pressure test, notational analysis was applied. All participants acquired specific badminton skills in 24 sessions over three months. In addition to specific badminton skills, the experimental group received the specific package of PST during 24 sessions (each session 20 min.) while placebo-control group received the same number of sessions about general information on badminton. The results of mixed ANOVA indicated that in all tests, the scores of experimental group were significantly higher than those of the placebo-control group, which indicated the effectiveness of PST on performance and learning of novice male badminton players. The results of this study extended the effectiveness of PST to learning new motor skills.